PENGARUH ALIRAN KAS BEBAS DAN SET KESEMPATAN INVESTASI TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI (Studi Empirik Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Burhanudin -; Siti Aisyah Hidayati; Muhamad Zainudin Tohri (Eco-Entrepreneur, 2019)
The reaserch examine about the influence of free cash flow and set of infesmnetopportunities toward company value with dividend policy as moderation variable thereaserch aim is to find out a) the influence of free cash flow toward company valueb) the influence invesment opportunities set toward company value c) whether thedividend policy is able to mederate the influence of free cash flow toward companyvalue d) whether the dividend policy is able to mederate the influence invesmentopportunities set toward company value, the reaserch sample is manufacturingcompany which listed in indonesia stock exchange period of 2012-2016, samplereceived trough sample survey based on criterion detemined thus, obtained 15companies become sample data analysis use simple linier regression analysis onhypothesis 1 and 2 later, double regression with modertated with moderatedregression analysis method (MRA) for hypothesis 3 and 4. Reaserch result showsthat free cash flow have a positive influence toward company value, invesmentopportunites set have possitive influence toward company value while moderatedregression analysis (MRA) shows that dividend policy weaken the influence betweenfree cash flow and company value, and dividend policy also weaken the influencebetween invesment opportunites set and company value.